2017
DOI: 10.1182/blood-2016-10-695965
|View full text |Cite
|
Sign up to set email alerts
|

Emerging treatments for classical myeloproliferative neoplasms

Abstract: There has been a major revolution in the management of patients with myeloproliferative neoplasms (MPN), and in particular those with myelofibrosis and extensive splenomegaly and symptomatic burden, after the introduction of the JAK1 and JAK2 inhibitor ruxolitinib. The drug also has been approved as second-line therapy for polycythemia vera (PV). However, the therapeutic armamentarium for MPN is still largely inadequate for coping with patients’ major unmet needs, which include normalization of life span (myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 120 publications
5
64
0
Order By: Relevance
“…It is prescribed as a targeted therapy for treatment of patients with primary MF, PV, and ET [155]. During clinical trials, it was shown to reduce spleen size, abdominal discomfort, bone pain, night sweats, and itching, as well as diminish the level of inflammatory cytokines in MPN patients.…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
“…It is prescribed as a targeted therapy for treatment of patients with primary MF, PV, and ET [155]. During clinical trials, it was shown to reduce spleen size, abdominal discomfort, bone pain, night sweats, and itching, as well as diminish the level of inflammatory cytokines in MPN patients.…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
“…Pharmacological inhibitors of MEK have shown considerable efficacy in BRAF ‐mutated metastatic melanoma, with case reports demonstrating significant clinical responses of these agents, such as trametinib, in NRAS ‐mutated haematological malignancies, including aCML with a similar neutrophilic hyperleucocytosis (Khanna et al , ). In context of the emerging array of treatments for MPN (Vannucchi & Harrison, ) such cases support the rationale for considering clinical trials of MEK inhibitors in the treatment of NRAS ‐mutated MPN.…”
mentioning
confidence: 91%
“…94 However, a few studies have examined at molecular level the effect of compounds that can target the mutant myeloproliferative clone. These studies have shown that pegylated or regular interferon a can induce significant reduction in mutant allele burden in patients with JAK2 (V617F)-mutant ET or PV, 95,96 and in those with CALR-mutant ET.…”
Section: Molecular Analysis Of Responsementioning
confidence: 99%